2003
DOI: 10.1579/0044-7447-32.3.176
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Recovery of Lakes in Southeastern Canada from the Effects of Acidic Deposition

Abstract: Reductions in North American sulfur dioxide (SO2) emissions promoted expectations that aquatic ecosystems in southeastern Canada would soon recover from acidification. Only lakes located near smelters that have dramatically reduced emissions approach this expectation. Lakes in the Atlantic provinces, Quebec and Ontario affected only by long-range sources show a general decline in sulfate (SO4(2-)) concentrations, but with a relatively smaller compensating increase in pH or alkalinity. Several factors may contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…However, this would have little sense for many reasons. First, in general: (i) studies cover very different temporal periods; (ii) the number of systems included in each individual study is very different, ranging from one intermittent stream [88] to a major comparison of 705 systems [66]; 33 of the published studies cover less than 10 systems and only 9 more than 100. Curiously, if all trends were pooled together, the existence of four earlier studies [64,66,71,73] covering a huge number of lakes in Canada and Scandinavia (1324 in total), where about 90% of the systems in each study showed no statistically significant trend, would probably give an overwhelming majority for the "non trend" category.…”
Section: Discussionmentioning
confidence: 99%
“…However, this would have little sense for many reasons. First, in general: (i) studies cover very different temporal periods; (ii) the number of systems included in each individual study is very different, ranging from one intermittent stream [88] to a major comparison of 705 systems [66]; 33 of the published studies cover less than 10 systems and only 9 more than 100. Curiously, if all trends were pooled together, the existence of four earlier studies [64,66,71,73] covering a huge number of lakes in Canada and Scandinavia (1324 in total), where about 90% of the systems in each study showed no statistically significant trend, would probably give an overwhelming majority for the "non trend" category.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in surface water DOC has been well documented in a number of regions in Europe and North America (Evans et al 2005;Skjelkvåle et al 2001;Kopáček et al 2006;Driscoll et al 2003;Jeffries et al 2003). Although the drivers associated with this increase are speculative, suggestions include decreased acidic deposition, increased temperatures owing to global warming, changes in hydrology and changes in land use (Evans et al 2005).…”
Section: Factors Confounding Recovery Of Surface Watersmentioning
confidence: 99%
“…Since the mid-1980s, sulfur deposition has decreased by ~40% as a result of legislation implemented in Canada (Eastern Canada Acid Rain Programme; 36) and the United States (Clean Air Act Amendments; 37) and the 1991 Canada-U.S. Air Quality Agreement (38). Surface-water chemistry has begun to recover (11,(39)(40)(41)(42). Additional reductions in sulfur deposition may occur in the future.…”
Section: Progress In North America?mentioning
confidence: 99%